The retail revolution : how Wal-Mart created a brave new world of business - Lichtenstein, Nelson (New York : Metropolitan Books, 2009)
Insightful, original, and steeped in the culture of retail life,'The Retail Revolution' draws on first-hand reporting from coastal China to rural Arkansas to give a fresh and necessary understanding of how Wal-Mart has transformed international commerce.
Sam Walton's world -- Supply and command -- The corporate culture -- Beat yesterday -- Unions : keep out! -- Wal-Mart's long march to China -- Discount stores in every clime? -- How Wal-Mart makes the rules -- Wal-Mart versus the world it has created.
Includes bibliographical references (p. [261]-293) and index.
Keywords: Wal-Mart (Firm) -- Management; Discount houses (Retail trade) -- United States -- Management; Retail trade -- United States -- Management